Housing quality and its impact on Acute Respiratory Infection (ARI) symptoms among children in Punjab, Pakistan. - Ammar Aftab; Amamah Noor; Memuna Aslam (Public Library of Science (PLoS), 2022)
Exposure to poor housing quality and household air pollution (HAP) are significant factors for morbidity and mortality in Pakistan. Children under five are particularly at risk of acute respiratory infections (ARIs). Globally, it has been estimated that 6.6 million children less than five years of age die every year from this disease. Little is known regarding the effect of HAP and poor housing quality on children's respiratory symptoms in Pakistan. Statistics concerning Pakistan's largest province, Punjab, are also not promising. Hence, an association between housing quality and respiratory symptoms among children under the age of five in Punjab has been studied in this paper. Using data from MICS 2017-18, logistic regression models were applied to the sample of 35000 children under the age of five living in poor housing quality. We estimated that acute respiratory infection (ARI) symptoms are higher among children when the floor of a house is made of natural material. However, the lower ARI symptoms were found among children living in a house with a wall made of natural material. On the other hand, we found that children residing in the western region of Punjab are at a higher risk of ARI symptoms. The findings remain consistent with the previous researchers. In addition to promoting increased access to quality housing material during construction activities, we suggest that critical community-based interventions are required to combat local issues and problems at the micro-level.